Electrochromic Performance of Nickel Oxide Thin Film: Synthesis via Electrodeposition Technique. Issue 1 (29th March 2016) - Kondalkar, Vijay V.; Patil, Pallavi B.; Mane, Rahul M.; Patil, Pramod S.; Choudhury, Sipra; Bhosal, Popatrao N.
Summary: Nanocrystalline Nickel oxide (NiO) thin films were electrochemically deposited onto ITO substrate at room temperature. In order to examine the optical absorption, crystal structure and surface morphology of deposited NiO thin films were characterized by means of UV–vis spectrophotometer, X‐ray diffraction (XRD) and scanning electron microscopy (SEM). The electrochromic (EC) performance of NiO thin film was investigated by means of cyclic voltammetry (CV), chronoamperometry (CA) and chronocoulometry (CC). The switching response of NiO thin film is found to be 5.62 s for coloration ( tc ) and 4.31 sec for bleaching ( tb ) with excellent reversibility. The electrochromic study shows highly reversible and the stable nature of electrochemically deposited NiO thin films which provides a versatile and promising application towards the fabrication of smart windows.